Romance languages : a historical introduction - Alkire, Ti, 1961-; Rosen, Carol G. (Cambridge ; New York : Cambridge University Press, 2010)
"Ti Alkire and Carol Rosen trace the changes that led from colloquial Latin to five major Romance languages, those which ultimately became national or transnational languages: Spanish, French, Italian, Portuguese, and Romanian. Trends in spoken Latin altered or dismantled older categories in phonology and morphology, while the regional varieties of speech, evolving under diverse influences, formed new grammatical patterns, each creating its own internal regularities. Documentary sources for spoken Latin show the beginnings of this process, which comes to full fruition in the medieval emergence of written Romance languages. This book newly distills the facts into an appealing program of study, including exercises, and makes the difficult issues clear, taking well motivated and sometimes innovative stands. It provides not only an essential guide for those new to the topic, but also a reliable compendium for the specialist"--
Machine generated contents note: Introduction; 1. The evolution of stressed vowels; 2. Early changes in syllable structure and consonants; 3. Consonant weakening and strengthening; 4. New palatal consonants; 5. More about vowels: raising, yod effects, and nasalization; 6. Verb morphology: the present indicative; 7. Verb morphology: systemic reorganization; 8. Noun and adjective morphology; 9. History and structure of Portuguese: an overview; 10. History and structure of Romanian: an overview; 11. Formation of the Romance lexicon; 12. Emergence of the Romance vernaculars; Suggestions for further reading; Works cited; Index of topics.
Bibliografija: str. 364-371
Kazalo
Keywords: Romanski jezici; Razvoj romanskih jezika; Romanski jezici; Kasni latinitet; Vulgarni latinitet